Pengembangan sistem informasi penjualan berbasis web pada toko wallpaper dengan metode prototype - Wahyuningtyas, Nuryansyah; Utomo, Listanto Tri (Journal of Information System and Application Development, 2024)
Sales information systems are a crucial component for companies, including Toko BIFFA Wallpaper, which requires increased efficiency in product sales. The current manual system causes various problems such as manual recording of transactions, income, and expenses, as well as ineffective archiving and management of daily and monthly financial reports. This research aims to build and implement a web-based sales information system to facilitate cashiers and owners of Toko BIFFA Wallpaper Kepanjen in managing, storing, and searching transaction data and reports. The method used is the prototype method, which includes needs analysis, rapid design, prototype construction, initial user evaluation, prototype improvement, and system development. The system is developed using PHP programming language and MySQL database, with testing conducted using the blackbox technique. The test results show that the system's appearance and features function well and meet user needs. This research concludes that the developed web-based sales information system significantly aids and facilitates cashiers and owners of Toko BIFFA Wallpaper Kepanjen in sales management, increasing efficiency and reducing manual errors.